Sagittal plane analysis of the spine and pelvis in degenerative lumbar scoliosis - Fei Han; Li Weishi; Sun Zhuoran; Ma Qingwei; Chen Zhongqiang (Journal of Orthopaedic Surgery, 2017)
Background: Previous studies have reported the normative values of pelvic sagittal parameters, but no study has analyzed the sagittal spino-pelvic alignment in degenerative lumbar scoliosis (DLS) and its role in the pathogenesis. Methods: Retrospective analysis was applied to 104 patients with DLS, together with 100 cases of asymptomatic young adults as a control group and another control group consisting of 145 cases with cervical spondylosis. The coronal and sagittal parameters were measured on the anteroposterior and lateral radiograph of the whole spine in the DLS group as well as in the two control groups. Results: Statistical analysis showed that the DLS group had a higher pelvic incidence (PI) value (50.5° ± 10.2°), than the normal control group (with PI 47.2° ± 8.8°) and the cervical spondylosis group (46.9° ± 9.1°). In DLS group, there were 38 cases (36.5%) complicated with degenerative lumbar spondylolisthesis, who had higher PI values than patients without it. Besides, the lumbar lordosis (LL) and sacral slope (SS) of DLS group were lower; the scoliosis Cobb’s angle was correlated with pelvic tilt (PT); thoracic kyphosis was correlated with LL, SS, and PT; and LL was correlated with other sagittal parameters. Conclusion: Patients with DLS may have a higher PI, which may impact the pathogenesis of DLS. A high PI value is probably associated with the high prevalence of degenerative lumbar spondylolisthesis among DLS patients. In DLS patients, the lumbar spine maintains the ability of regulating the sagittal balance, and the regulation depends more on thoracic curve.